(untitled) (ESPES The Slovak Journal of Aesthetics, 2025)
This article introduces the aesthetics of posthumanism as a genuine trend in philosophical aesthetics that emerged in the early decades of the 21st century. Engaging with an innovative imagination of the cohabitation of various life forms, the aesthetics of posthumanism rethinks interspecies encounters across both cultural and natural environments, prompting us to consider ethically motivated images of environmental awareness and creative adaptation. Building on phenomenological, deconstructive, and schizoanalytic methodological insights, this article aims to highlight a turning point in contemporary aesthetic research that questions our anthropocentric, speciesist prejudices and presents them as obsolete in a world shaped by the global environmental crisis. To address the complexity of this topic, the article presents contributions that map various approaches to the ‘posthuman situation’ in the artistic and philosophical imagination of contemporary human identity. The first set of referred texts targets the multifaceted – environmental, social, and technological – disaster caused by the speciest, self-centred humanism of the modern era, and the subsequent rupture of posthumanist art from it. This aesthetic perspective gives rise to resistance through posthumanist engagement. The second set of references addresses various problems related to anthropocentrist aesthetics. By introducing thinkers who articulate distinct viewpoints on the politics of aesthetic imagination, this article presents two contrasting approaches to contemporary visuality: while one group welcomes the environmentally caring approach of post-anthropocentrism, the other advocates preserving the anthropocentric one.